Paperless reporting and electronically verifying clinical investigations. Issue 5 (3rd June 2014) - Hung Sun, Cheng; Lew, Thomas; Tan, Doris; Yin Hoi, Shu; Khandan and, Raj; Hwee Poi, Choo; Surender, Reddy; Tay, Shirley; Wan, Gervais; Lee, Y.S.; Lee Lim, Lee; Solikin, Handi; et al.
Abstract : Purpose: – The purpose of this paper is to outline considerations and steps taken to introduce electronic reporting and verification from systems design and multidisciplinary collaborations to gap analysis and devising solutions. It also evaluates carefully placed forcing functions' impact on verification rates. Design/methodology/approach: – A multidisciplinary workgroup was formed to stop print and establish electronic reporting. The electronic verification's success was assessed by weekly activity analysis. Findings: – Introducing a verification forcing function markedly improved verification activity. Thereafter, non-verified results stabilized at 7 percent up to 75 weeks post-implementation. Practical implications: – This paper illustrates how results reporting and verification could be implemented in a tertiary hospital using a mixed electronic and paper record. Factors that were critical to success include stakeholder engagement and applying systems design that focussed on patient safety as a key priority. The electronic reporting system was augmented by strategically inserted forcing functions, clear clinical-responsibility lines and ancillary alert systems. Originality/value: – The systems design method's value in managing non-critical but abnormal results appears to have been under-appreciated. This paper describes how systems design could be used to improve health information delivery and management.